The risk of falls among the aging population: A systematic review and meta-analysis - Xu, Qingmei; Ou, Xuemei; Li, Jinfeng (Frontiers in Public Health, 2022)
Aims: To clarify the risk factors of Fall to help older adults avoid severe consequences of it. Methods: We searched the PubMed, Embase, and Cochrane Library databases to identify all trials and compared results using items “fall”, “drop”, “risk factors”, “predict factors”. And the population is divided into two groups “Fall group” and the “control group”, then compare the differences in characteristics, lifestyle, and comorbidities among those. Results: There are 30 papers included in this study, and 21 factors have been analyzed. The final data demonstrated: Age, education, Polypharmacy, Malnutrition, Single, living in rural, smoking and drinking will make aging more preferred to suffer fall; Cardiac disease, Hypertension, Diabetes, Stroke, Frailty, fall history, Depression, Parkinson’s disease and Pain can improve the risk of frailty among the old population. Conclusion: Characteristics, comorbidities, and lifestyle can impact the occurrence of Fall, and relevant influencing factors should be paid attention to.